Depressive symptoms in type II diabetics of a tertiary care hospital in southern India - B. S., Nagaraja; K. R., Divya Sharma (International Journal of Advances in Medicine, 2018)
Background: International diabetes federation has highlighted that “the diabetic epidemic is here and threatens to overwhelm health systems if unchecked’’. The global prevalence of diabetes among adults has risen from 4.7% in 1980 to 8.5% in 2014. India unfortunately tops the list of countries with the largest number of people living with diabetes. Diabetes and depression are independent risk factors for one another and both are associated with increased risk of cognitive decline. Prevalence of depression is doubled in Diabetes mellitus, and also appears to vary by type of Diabetes mellitus, race/ethnicity, and duration of diabetes and associated debilitating complications and co-morbidities. Various studies using different methodology have revealed varying prevalence of depression. Data on this association of Diabetes and depression is limited in Indian context. Methods: This is a cross sectional study conducted on type 2 Diabetics attending outpatient department of Victoria and Bowring and Lady Curzon Hospital. Data regarding duration and treatment of diabetes, HbA1c levels and associated comorbidities were collected along with basic particulars of the patient. Becks depression questionnaire were used for analyzing the depressive symptoms. Results: A total of 302 diabetic patients were included in the study, out of which Males were 156 and Females were 146. Severe depressive symptoms were found in 18.21% of diabetics, and moderate depressive symptoms were found in 39.74% of study population. It is also found that the significant predictors of these depressive symptoms are increasing age, longer duration of diabetes, treatment intensity. Conclusions: In conclusion depressive symptoms are more common in diabetic subjects compared to non-diabetic population. Especially this increases with duration of diabetes and uncontrolled sugars. Hence there is a need to screen all diabetes subjects for depression.